Mutations in the structural genes for eukaryotic initiation factors 2 alpha and 2 beta of Saccharomyces cerevisiae disrupt translational control of GCN4 mRNA. - Williams, N P (1989)
The SUI2 and SUI3 genes of Saccharomyces cerevisiae encode the alpha and beta subunits, respectively, of translation initiation factor eIF-2 (eukaryotic initiation factor 2). Previously isolated mutations in these genes restore expression from his4 mutant alleles lacking an ATG initiation codon. The SUI mutations also lead to increased levels of HIS4 mRNA. We show that the latter phenotype exists because the SUI mutations elevate expression of GCN4, an activator of HIS4 transcription. Increased GCN4 expression in the SUI mutants occurs independently of the GCN2 and GCN3 gene products that are normally required to stimulate translation of GCN4 mRNA under conditions of amino acid starvation. Derepression of GCN4 expression in the SUI mutants requires the multiple AUG codons in the leader of the GCN4 transcript that normally mediate its translational control by amino acid availability. In these respects, the SUI mutations resemble mutations in GCD genes whose products function as translational repressors of GCN4. Thus, in addition to its general role in AUG start codon selection, eIF-2 appears to be an important factor in GCN4 translational control. We also show that deletion of GCN3 in sui2-1 strains is lethal, suggesting that GCN3 contributes to eIF-2 alpha function in addition to its role as a translational activator of GCN4.